2013
DOI: 10.1108/01409171311314969
|View full text |Cite
|
Sign up to set email alerts
|

Marketing an Islamic index: perceived value of KMI30 Index

Abstract: PurposeThe purpose of this paper is to understand if there is a customer perceived value for shareholders in investing in Islamic stocks, by using KMI30 index of Karachi Stock Exchange as a case study. The findings are then used to devise a conceptual model, highlighting the value of an Islamic branded index and for companies included on the index for market participants, Shari'ah‐compliant firms, and governments.Design/methodology/approachThis is an exploratory research paper. A detailed literature review is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 84 publications
1
4
0
Order By: Relevance
“…Table 10 shows that in the group of company shares included in the index, a significant positive market reaction only occurred in the group of company shares included in JII, while company shares included in the LQ45 Index and the SRI-Kehati Index did not find any positive market reaction. The positive market reaction to company shares included in JII is in line with the results of Sayani and Balakrishnan's (2013) research which found that there was a positive market return and lower volatility when the company entered into the Islamic Index (KMI30) on the Karachi Stock Exchange.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Table 10 shows that in the group of company shares included in the index, a significant positive market reaction only occurred in the group of company shares included in JII, while company shares included in the LQ45 Index and the SRI-Kehati Index did not find any positive market reaction. The positive market reaction to company shares included in JII is in line with the results of Sayani and Balakrishnan's (2013) research which found that there was a positive market return and lower volatility when the company entered into the Islamic Index (KMI30) on the Karachi Stock Exchange.…”
Section: Discussionsupporting
confidence: 80%
“…Oberndorfer et al (2013) further stated that this implies that investors do not reward (rewarded) companies that have higher social (environmental) performance (which can actually potentially benefit from a better company reputation and cost savings in long-term). Sayani and Balakrishnan (2013) examined the performance of company shares in the KMI30 Index on the Karachi Stock Exchange. The results of his research show that company shares included in the KMI30 Index have a positive market return and a relatively low level of stock volatility when compared to the KSE100 Index.…”
Section: Efficient Market Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…IM ethics have a very significant positive influence on brand credibility (Al‐Nashmi & Almamary, 2017), for example—marketers can use halal certification as a brand association in IM (Rajagopal et al., 2011). It is noteworthy that like CB, Islamic brands can assume different personalities: purity, safety, sophistication and righteousness (Ahmed, 2015), marketers can communicate the perceived value of brand to create brand image and brand loyalty which increases the performance of the entire company (Sayani et al., 2013).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Islamic finance also dominates Muslim marketing literature with works by (Alserhan, 2010b; Fatema et al., 2018; Ireland, 2018; Jamshidi & Hussin, 2016; Ltifi et al., 2016; Mahdzan et al., 2017; Maulan et al., 2016; Sayani et al., 2013; Setyobudi et al., 2016; Wahyuni & Fitriani, 2017; Yeniaras, 2016; Yildiz et al., 2014; Zinser, 2019) publishing works with varied focus, for example—emphasizing customer loyalty (Ireland, 2018; Wahyuni & Fitriani, 2017); consumer behaviour and attitudes towards banking and finacial sector (Fatema et al., 2018; Jamshidi & Hussin, 2016; Ltifi et al., 2016; Mahdzan et al., 2017; Yeniaras, 2016; Yildiz et al., 2014).…”
Section: Findings and Discussionmentioning
confidence: 99%